1982
DOI: 10.1042/bj2070459
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of three forms of glutathione S-transferase A. A comparative study of the major YaYa-, YbYb- and YcYc-containing glutathione S-transferases

Abstract: Rat liver glutathione S-transferases have previously been defined by their elution behaviour from DEAE-cellulose and CM-cellulose as M, E, D, C, B, A and AA. These enzymes are dimeric proteins which comprise subunits of mol.wt. 22 000 (Ya), 23 500 (Yb) or 25 000 (Yc). Evidence is presented that YaYa protein, one of two previously described lithocholate-binding proteins which exhibit transferase activity, is an additional enzyme which is not included in the M, E, D, C, B, A and AA nomenclature. We therefore pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…GST activity towards 1-chloro-2,4-dinitrobenzene (CDNB) and glutathione peroxidase activity with cumene hydroperoxide were measured at 340 nm with the Cobas Fara II Chemistry System (Hoffmann-La Roche Ltd, Basel, Switzerland) [32,33]. In all enzyme activity assays, the non-enzymic reaction rate was measured and subtracted from the overall reaction rate.…”
Section: Scheme 1 Biotransformation Of Dcm By the Gst-mediated Conjugmentioning
confidence: 99%
“…GST activity towards 1-chloro-2,4-dinitrobenzene (CDNB) and glutathione peroxidase activity with cumene hydroperoxide were measured at 340 nm with the Cobas Fara II Chemistry System (Hoffmann-La Roche Ltd, Basel, Switzerland) [32,33]. In all enzyme activity assays, the non-enzymic reaction rate was measured and subtracted from the overall reaction rate.…”
Section: Scheme 1 Biotransformation Of Dcm By the Gst-mediated Conjugmentioning
confidence: 99%
“…On the basis of decreasing electrophoretic mobilities, three pro-tein bands were resolved and were designated Ya, Yb, and Yc (17). Subsequent studies showed that the Ya and Yc bands represent class alpha GST, whereas the Yb band represents class mu GST (18,19). These findings were used to devise a class-based nomenclature for GST subunits (20).…”
mentioning
confidence: 99%
“…245 Abbreviations used: GST, glutathione S-transferase; CDNB, I-chloro-2,4-dinitrobenzene; DCNB, 1,2-dichloro-4-nitrobenzene; PAGE, polyacrylamide-gel electrophoresis. Hayes & Clarkson (1982). Assays for microsomal GST, with CDNB as substrate, were performed manually as described by Morgenstern et al (1980).…”
Section: Buffersmentioning
confidence: 99%